The Aesthetic World of Mushegh Galshoyan’s Essays - YERVANDYAN, ZUKHRA (Bulletin of Yerevan University B: Philology, 2021)
Having studied the essay literature created by Galshoyan, in the article Z.Yervandyan presents Galshoyan’s conceptions of the principles of world and existence, the role of the homeland constructing work in them, as well as those meditations of the author that underline his worshipping love to creating people and to the nature, to the earth – the archetype of homeland. The author of the article mentions that the heroes of Galshoyan’s essays are the persons-symbols depicting some epoch: they deeply carry the psychology and mentality of ruling time period and by this means, for the interested one, they may depict on a very wide canvas the panorama of Armenian existential reality of that period, with geographically multisided spreading.